Translatonomics: Teaching English for Economics through Translation Practice - Shafa Firda Nila; Teguh Susanto (Metathesis: Journal of English Language, Literature, and Teaching, 2018)
This study aims to propose a method called Translatonomics to teach English for Economics through translation practice to encourage the students to understand English contextually. The participants are 25 students of Management and 25 students of Accounting study program. The research is conducted firstly to identify the ability of the students to understand English text about Economics and translate it into Bahasa Indonesia, then to introduce contextual translation from translating simple sentences, short paragraphs, and text. The result shows that most students still have high dependency on instant translation such as Google Translate and do not try to relate the context as they do not understand the text. Therefore, it is important to encourage the students to understand the text contextually and one of the ways is through translation practice. In Translatonomics, the translation practice section is divided into three parts: translating simple sentences, translating short paragraphs, and translating texts. On the first part, students are encouraged to translate English simple sentences about Economics. Then, on the second part, students are encouraged to translate English short paragraphs extracted from Economics texts. Finally, on the third part, students are encouraged to translate some Economics texts.